Ein Epochenbruch: Die neuen globalen Proteste zwischen Organisation und Bewegung - Azzellini, Dario (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2014)
The article works out common features among the new global movements that formed during the contemporary multiple crisis around the world, and traces back the beginning of this ‘anti-representative’ uprisings to a first wave of protest in Latin America since the late 1980’s. Content, focus and organizational forms of the new movements point at a historical break as 1848, the early 20th Century or 1968.